Increased Diabetic Neuropaty Scores and Their Relationship with Body Mass Index - Nurul Aktifah; Firman Faradisi; Dwi Fijianto (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The increasing prevalence of diabetes has an additional impact on sufferers in the form of complications of diabetes mellitus. One of the complications that often occurs is diabetic neuropathy in the foot area where this complication can be caused by various factors. This study aims to determine whether body mass index (BMI) has a relationship in increasing the occurrence of diabetic neuropathy in DM patients. This study uses a descriptive analytic research design with a cross sectional research design. The sample of this research was taken by purposive sampling with a total of 92 respondents. Body mass index was obtained by measuring the respondent's height and weight, while diabetic neuropathy was carried out by examining complaints of neuropathy in the feet. The results of the research analysis showed that most of the respondents' BMI values were in the fat category (66.7%). The analysis test using chi suare obtained a p value of 0.021, which means that there is a relationship between body mass index and the severity of diabetic neuropathy scores. The higher the respondent's BMI value, the higher the diabetic neuropathy score they experienced. From the results of this study, it is recommended for diabetics to reduce BMI to the normal range either through exercise or proper diet.